Peningkatan Keterampilan Musikalisasi Puisi Dengan Model Pembelajaran Berbasis Proyek Berbantuan Media Sosial Sma Negeri 14 Semarang - Nur Aini, Miladia; Ulumuddin, Arisul; Tri Pudjowati, Anis (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2024)
Education is one of the efforts for students to acquire intelligence in aspects of knowledge, skills, and positive attitudes through planned development of potential. Education is an important component in life. One of the lessons given at school is the musicalization of poetry. There is a problem where students lack confidence in displaying poetry musicals, therefore researchers use Instagram social media. The purpose of this study is to describe the use of project-based learning models assisted by social media can improve learning outcomes from students. This research is a classroom action research with a total of 33 students. As a result of the study, students when practicing musicalization of poems uploaded on Instagram social media became more confident and got better results.